Evidence for protosolar graphene in Allende and QUE 94366 CV3 meteorites. (1st September 2021) - Giri, Chaitanya; Steele, Andrew; Fries, Marc
Abstarct: Nanoscale graphene morphologies are reported in the Allende and QUE 94366 CV3-type carbonaceous chondrites via Confocal Raman Imaging Spectroscopy. These morphologies are found embedded in the refractory calcium-aluminum-rich inclusion (CAI) rims in Allende and within a chondrule inclusion in QUE 94366. Earlier investigation already revealed graphite whiskers (GWs) presence in both these meteorites. Further inspection of the meteoritic sections, coupled with advancements in the knowledge of carbon materials, reveal a re-interpretation of Raman features of a subset of the reported GWs and newer analyzed features as graphene. This meteoritic graphene perhaps originated from the same protosolar carbon reservoir that synthesized the GWs. The graphene was most likely synthesized concurrent to the inclusions and CAIs, in a high-temperature zone near the proto-Sun and during the solar system's earliest eon. However, in the case of Allende we cannot totally rule out synthesis during later aqueous alteration of the original mineral CAI assemblage. Highlights: Nanoscale graphene is found embedded in refractory inclusions of two different CV3 meteorites, Allende and QUE 94366. The detected graphene could be as old as the calcium-aluminum-rich inclusions, and perhaps synthesized in the inner protosolar nebula, dating around 4.5 billion years. The graphene detected here could be the building block of graphite whiskers already found in the same refractory inclusion and the two could be remnants of a protosolar reservoir of carbon allotropes. Such carbon allotropes resemble morphologies that have been theorized to thermalize ambient radiation to generate the ~3 ​K microwave background.